PERFORMANCE ANALYSIS FOR DIRECTION-FINDING CIRCULAR ANTENNA ARRAY - Svyatoslav V. Ballandovich; Grigory A. Kostikov; Liubov M. Liubina; Mikhail I. Sugak (Известия высших учебных заведений России: Радиоэлектроника, 2018)
This paper considers circular antenna arrays comprised of symmetrical dipole radiators applied in communication, navigation and monitoring systems. Despite their widespread use, a number of significant issues is underinvestigated. Among them are frequency dependence of the antenna factor (the ratio of the electric field intensity module to the voltage amplitude at the load connected to the output terminals) of the circular antenna array elements in the correct electrodynamic setting. The purpose of this paper is to analyse the antenna factor frequency dependence of a single dipole antenna with different geometry and load both in free space and as circular antenna element. The estimation of phase difference error between the circular antenna array elements caused by their cross coupling is also of interest.Specific expressions are obtained for the antenna factor of the dipole antenna for single-mode and three-mode approximations. The limits of their applicability in frequency band are considered. The solution to the coupled integral equations is obtained using the Galerkin method with piecewise sinusoidal current distribution and with an arbitrary number of basis functions for eight- and four-element circular antenna array. This solution may be generalized to an arbitrary number of circular antenna array elements. It is demonstrated that to improve the antenna factor frequency dependence it is advisable to use dipole antennas with high-resistance load, as well as with large diameter. Phase errors for different circular antenna array element signals are considered with respect to the reference element. The dependence of these phase errors on the circular antenna array geometry is presented. It is concluded that there are significant oscillations of the antenna factor when the dipole is the part of the circular antenna array. They are caused by cross coupling between the circular antenna array elements, which significantly depend on the element spacing. The results presented may be of interest to phase direction finder development engineers.